Adaptive image segmentation reveals substantial cortical bone remodelling during early fracture repair - Alireza Ariyanfar; Karina Klein; Brigitte von Rechenberg; Salim Darwiche; Hannah L. Dailey (Computer Methods in Biomechanics and Biomedical Engineering: Imaging & Visualization, 2024)
The goal of this study was to develop an image analysis algorithm for quantifying the effects of remodelling on cortical bone during early fracture healing. An adaptive thresholding technique with boundary curvature and tortuosity control was developed to automatically identify the endocortical and pericortical boundaries in the presence of high-gradient bone mineral density (BMD) near the healing zone. The algorithm successfully detected boundaries in more than 47,000 microCT images from 12 pairs of healing ovine osteotomies and intact contralateral tibiae. Resampling techniques were used to achieve data dimensionality reduction on the segmented images, allowing characterisation of radial, circumferential, and axial distributions of cortical BMD. Local (transverse slice) and total (whole bone) remodelling scores were produced. These surrogate measures of cortical remodelling derived from BMD revealed that cortical changes were detectable throughout the region covered by callus and that the localised loss of cortical BMD was highest near the osteotomy. Total remodelling score was moderately and significantly correlated with callus volume and mineral composition (r > 0.64, p < 0.05), suggesting that the cortex may be a source of mineral needed to build callus.